2014
DOI: 10.1159/000365440
|View full text |Cite
|
Sign up to set email alerts
|

The Use of a Tablet Computer Platform to Optimize the Care of Patients Receiving Peritoneal Dialysis: A Pilot Study

Abstract: Background: Peritoneal dialysis (PD) affords patients increased independence and improved quality of life. However, the lack of more frequent monitoring may compromise outcomes and decrease wider uptake of this modality. This study uses a novel tablet computer-based interface to allow real-time monitoring and two-way communication to better link PD patients with a dialysis center and care providers. Methods: A tablet computer with an application that allows enhanced monitoring of all aspects of PD was given to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
79
0
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(90 citation statements)
references
References 7 publications
0
79
0
11
Order By: Relevance
“…These results are in accordance with Nayak et al [13]: they speculated that RM of patients on APD offers benefits of real-time monitoring of the therapy, assuring patient safety through the surveillance of critical portions of the treatments, and, on the other hand, enabling early detection of noncompliance [10]. A system with 2-way communications and with an interactive interface allows a fast “troubleshooting” for problems: the physicians can change the prescription online, reducing the frequency of in-person visits to a PD center [13, 14]. …”
Section: Discussionmentioning
confidence: 99%
“…These results are in accordance with Nayak et al [13]: they speculated that RM of patients on APD offers benefits of real-time monitoring of the therapy, assuring patient safety through the surveillance of critical portions of the treatments, and, on the other hand, enabling early detection of noncompliance [10]. A system with 2-way communications and with an interactive interface allows a fast “troubleshooting” for problems: the physicians can change the prescription online, reducing the frequency of in-person visits to a PD center [13, 14]. …”
Section: Discussionmentioning
confidence: 99%
“…Many of these benefits, although intuitive, are currently hypothetic and few clinical studies (Table 2 lists clinical studies in this area) have demonstrated specific benefits of telehealth services for patients with ESRD. The current literature in this are single center experiences utilizing telemedicine for the care of patients receiving HD (14-23) or PD (24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Thus, studies that address the utility of telehealth and include endpoints of interest to patients, providers, and payers (i.e., improvements in mortality, lowering of readmission rates, improved quality of life, and cost savings) are needed.…”
Section: Opportunities For the Care Of Patients With Esrdmentioning
confidence: 99%
“…Telehealth platforms that utilize video conferencing may allow the care team to monitor patients while they perform self-care, provide feedback on patient techniques, and institute continuous education programs that help ensure survivability of the home dialysis technique through avoidance of complications such as peritonitis, catheter exit site infections, or needle-stick injuries. For example, a telehealth system for patients receiving PD has been reported that embeds best-practice care steps into a tablet computer application as well as providing the ability for the care team to monitor the patient performing PD exchanges (27). Patients using this system reported high degrees of satisfaction with these features.…”
Section: Ongoing Training Counseling and Education Opportunitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It allows for accurate home monitoring of patients enabling the team to improve care through prevention and early identification of problems, with consequent timely interventions. In this view, TM and RM may have important reflections on prognosis, outcomes, and quality of life [4]. RM has proved to be useful in chronic diseases where frequent controls are particularly useful such as heart failure, diabetes, and hypertension [5,6].…”
Section: Introductionmentioning
confidence: 99%